Pengaruh Luxury Brand dan Perceived Value terhadap Brand Attachment Mahasiswa Pengguna Iphone di Kota Medan : Penelitian - Indri Prasetia Ningsih; Onan Marakali Siregar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The rapid development of digital technology has led to an increase in smartphone usage among students, with the iPhone emerging as a dominant brand in the luxury category. iPhone is not only chosen for its technological quality and advanced features but also for the symbolic value and prestige it conveys. Many students believe that owning an iPhone enhances their social status and reflects a modern lifestyle. This study aims to analyze the influence of luxury brand and perceived value on brand attachment among iPhone-user students in Medan. The research examines the effect of each variable both partially and simultaneously. The luxury brand variable includes perceptions of exclusivity, prestige, and social recognition, while the perceived value variable captures students’ assessment of the benefits, quality, and emotional or social value of using an iPhone. A quantitative research method with an associative approach was applied in this study. The sample consisted of 100 iPhone-user students selected through purposive sampling. Data were collected using questionnaires on google form and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing to determine the influence of each variable.The results of the study indicate that both luxury brand (X1) and perceived value (X2) have a significant positive effect on brand attachment (Y), both partially and simultaneously. The multiple linear regression analysis shows a high level of significance, with an adjusted R² value of 0,590, indicating that 59% of the variation in brand attachment can be explained by the two independent variables. This confirms that students’ emotional connection to the iPhone brand is strongly influenced by their perception of its luxury and overall value.